Flame retardant loss-resistant efficient flame-retardant wood and preparation method thereof

By impregnating nitrogen and phosphorus flame retardant in wood and applying Si-rich flame retardant to the surface, the problem of easy loss of nitrogen and phosphorus flame retardant in high humidity environments is solved, and the efficient flame retardant performance of wood and the combustion characteristics of low smoke and low carbon monoxide are achieved.

CN119567374APending Publication Date: 2025-03-07ANHUI AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411758952.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing nitrogen and phosphorus flame retardants are easily lost in high humidity environments, causing wood to lose its flame retardant properties and produce harmful gases such as flue gas and carbon monoxide during combustion.

Method used

The two-step method is used to prepare flame retardant wood. The first step is to impregnate nitrogen and phosphorus flame retardant in the wood, and the second step is to apply Si-rich flame retardant on the surface of the wood to form a hydrophobic coating to prevent the loss of nitrogen and phosphorus flame retardant.

Benefits of technology

The loss resistance of nitrogen and phosphorus flame retardant is achieved, the efficient flame retardant performance of wood is maintained, and the production of very little flue gas and carbon monoxide under fire conditions is generated, reducing the fire hazard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567374A_ABST
    Figure CN119567374A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wood processing, and particularly relates to flame retardant loss-resistant efficient flame-retardant wood and a preparation method thereof.The preparation method comprises the steps that phytic acid and amino acid are put into a reaction container, and heating, condensation and reflux are conducted to obtain NP flame retardant liquid; the preparation method comprises the following steps: mixing n-hexane, polydimethylsiloxane, 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane and nano silicon dioxide according to a certain sequence and proportion, putting the mixture into a reaction container, and stirring to obtain Si-rich flame retardant liquid; the preparation method comprises the following steps: sequentially dipping the NP flame retardant into raw material wood, coating the Si-rich flame retardant on the raw material wood, drying in the shade, drying, and balancing water to obtain the flame-retardant wood. According to the invention, the synergistic flame-retardant and loss-resistant effects of the NP flame retardant and the Si-rich flame retardant are utilized, so that the purposes of flame retardance, smoke suppression and loss resistance are achieved, and the application of the nitrogen-phosphorus-silicon composite flame retardant as a wood flame retardant is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood processing, and in particular relates to a flame retardant anti-loss type high-efficiency flame retardant wood and a preparation method thereof. Background Art

[0002] As a natural, biodegradable and environmentally friendly material, wood plays an important role in people's lives. However, its flammability greatly limits its application. Therefore, while giving full play to the excellent properties of wood, modifying it to improve its flame retardant properties and expand the scope of application of wood is an important way to save wood resources and meet the various functional needs of people's lives.

[0003] With the development and progress of the times, people have put forward higher requirements for the environmental protection of flame retardants, but there are not many types that can be put into practical application at present. Nitrogen-phosphorus flame retardants are low in price, good in solubility, and good in flame retardant properties, so they are the most commonly used wood flame retardants. However, nitrogen-phosphorus flame retardants have high hygroscopicity. When the flame-retardant wood prepared by them is in a high humidity environment, the nitrogen-phosphorus flame retardant can easily migrate to the surface of the wood with the action of moisture; when the flame-retardant wood contacts water, the nitrogen-phosphorus flame retardant is easily soluble in water. Once the nitrogen-phosphorus flame retardant migrates to the surface of the wood or runs away, the flame-retardant wood will not have reliable flame retardant properties. In addition, compared with untreated natural wood, nitrogen-phosphorus flame retardants will produce more harmful gases such as smoke and carbon monoxide while preventing aerobic combustion of wood.

[0004] In view of this, the inventors hope to provide a flame retardant anti-loss type high-efficiency flame retardant wood and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to overcome the above problems existing in the prior art and to provide a flame retardant anti-loss type high-efficiency flame retardant wood and a preparation method thereof.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0007] The present invention provides a method for preparing a flame retardant anti-loss type high-efficiency flame retardant wood, comprising the following steps:

[0008] S1. Put the phytic acid solution and the amino acid solution into a reaction container according to a certain ratio, heat and condense the solution at a temperature of 20 to 80° C. for 0.5 to 4 hours, and then add ammonia water to adjust the pH value of the mixed solution to 5 to 7 to obtain a flame retardant solution A for standby use;

[0009] S2, add polydimethylsiloxane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to n-hexane in sequence, stir at 20-80°C for 0.5-4h, then add nano-silicon dioxide, mix well, and stir at 20-80°C for 0.5-4h to obtain flame retardant solution B for standby use;

[0010] S3, pre-treating the raw wood to obtain pre-treated wood;

[0011] S4, firstly use the flame retardant solution A to impregnate the pretreated wood, then dry the obtained impregnated wood, and then use the flame retardant solution B to coat the obtained dried wood to obtain flame retardant wood.

[0012] Furthermore, in step S1, the mass concentration of phytic acid in the phytic acid solution is 70 wt %, and the mass concentration of amino acids in the amino acid solution is 10 wt %.

[0013] Furthermore, in step S1, the molar ratio of phytic acid in the phytic acid solution to amino acid in the amino acid solution is 1:1-2; and the amino acid in the amino acid solution is at least one of lysine, arginine, glutamic acid, threonine, and phenylalanine.

[0014] Furthermore, in step S2, the mass ratio of n-hexane, polydimethylsiloxane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane is 20:1-5:0.1-0.5.

[0015] Furthermore, in step S2, the mass ratio of nano-silica to polydimethylsiloxane is 0.1-0.5:1.

[0016] Furthermore, in step S3, the species of raw wood is poplar; the specific operation of pretreatment is: sawing the newly felled poplar wood into boards with a thickness of ≤50 mm, exposing them to air to dry until the moisture content is ≤50%, and then placing the boards in a forced air drying device and drying them at a temperature of 30-80°C to a moisture content of ≤15%.

[0017] Furthermore, in step S4, the specific operation of the impregnation treatment is: completely immersing the pretreated wood in a pressure impregnation tank filled with flame retardant solution A, the impregnation temperature is controlled at 20 to 80° C., the impregnation pressure is controlled at -0.1 to 0.05 MPa, and the impregnation time is controlled at 0.5 to 4 hours.

[0018] Furthermore, in step S4, the specific operation of the drying treatment is: firstly, the impregnated wood obtained by the impregnation treatment with the flame retardant solution A is shade-dried for 2 to 4 hours, and then dried at a temperature of 40°C.

[0019] Furthermore, in step S4, the specific operation of the coating treatment is: uniformly coating the flame retardant solution B on the outer surface of the dried plate obtained by the drying treatment, with a coating amount of 0.20 to 0.30 g / cm 2 ; Then dry the coated wood in the shade for 2 to 4 hours and dry it at 40°C; then place the wood in a constant temperature and humidity chamber and carry out moisture balance at 22°C and 65% humidity, with the balance time ≥80 hours.

[0020] The present invention also provides a flame retardant anti-loss type high-efficiency flame retardant wood, which is prepared by the above-mentioned preparation method.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention retains the advantages of nitrogen-phosphorus flame retardants and realizes the anti-loss of flame retardants through a two-step method: the first step is to impregnate the nitrogen-phosphorus flame retardant into the wood to provide flame retardant properties, and the second step is to place a flame retardant coating with flame retardancy, smoke suppression, and hydrophobicity on the surface of the wood. The hydrophobic coating ensures that the internal nitrogen-phosphorus flame retardant is not easy to lose, and the silicon element in the hydrophobic coating further forms a flame retardant and smoke suppression synergistic effect with the nitrogen-phosphorus flame retardant.

[0023] 2. The flame retardant wood prepared by the present invention still has high flame retardancy after repeated immersion in water, and the loss of modifier is small; the flame retardant wood cannot be ignited in the air and has good flame retardancy; the combustion reaction of the flame retardant wood under fire conditions (780°C) produces very little smoke and carbon monoxide, reducing the fire hazard.

[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0026] Figure 1 The figure is the test result of moisture absorption and loss resistance of modified wood;

[0027] Figure 2 This is the test result diagram of ignition time and limiting oxygen index of modified wood;

[0028] Figure 3 This is the test result diagram of total heat release of modified wood in cone calorimetry test;

[0029] Figure 4 This is a graph showing the total smoke release test results of modified wood in a cone calorimeter test;

[0030] Figure 5 This is a graph showing the test results of carbon monoxide release rate of modified wood in a cone calorimetry test. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The invention provides a method for preparing flame retardant anti-loss type high-efficiency flame retardant wood, wherein phytic acid and amino acid are put into a reaction container, heated, condensed and refluxed to obtain NP flame retardant liquid; n-hexane, polydimethylsiloxane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane and nano silicon dioxide are mixed in a certain order and proportion and put into a reaction container, and stirred to obtain Si-rich flame retardant liquid. NP flame retardant and Si-rich flame retardant are sequentially coated on raw wood, and flame retardant wood can be prepared through shade drying, drying and moisture balance.

[0033] The present invention utilizes the synergistic flame retardant and anti-loss effect of NP flame retardant and Si-rich flame retardant to achieve the purpose of flame retardant, smoke suppression and anti-loss, and expands the application of nitrogen-phosphorus-silicon composite flame retardant as wood flame retardant.

[0034] Poplars are selected as the raw material wood in the following embodiments and comparative examples 2-3. The poplar variety is Jianghuai No. 1 Poplar, which is selected from the Taihe County Forest Farm Experimental Base in Anhui Province. The Taihe County Forest Farm Experimental Base in Anhui Province (35°10'~35°21'N, 113°40'~113°26'E) belongs to the temperate monsoon climate, with sufficient sunshine, cold winter and hot summer, warm spring and cool autumn, distinct four seasons, an average annual temperature of 12.8~14.8℃, an average annual precipitation of 600~700mm, and a frost-free period of 200 days. The age of the selected poplars is 7 years, the tree height is 24m, and the diameter at breast height is 30.5cm. The raw material wood is a poplar wood without decay, insect bites, stuttering, or cracking.

[0035] The relevant specific embodiments of the present invention are:

[0036] Example 1

[0037] This embodiment provides a flame retardant anti-loss type high-efficiency flame retardant wood, and the preparation steps are as follows:

[0038] 1) Preparation of flame retardant solution A

[0039] Phytic acid and arginine were placed in a three-necked flask at a molar ratio of 1:1 and heated at 50°C for condensation and reflux for 2 hours to obtain NP flame retardant liquid. Ammonia water was added to adjust the pH value of the mixed solution to 6, which was flame retardant solution A.

[0040] 2) Preparation of flame retardant solution B

[0041] n-Hexane: polydimethylsiloxane: 1H,1H,2H,2H-perfluorodecyltriethoxysilane were mixed in a mass ratio of 20:1:0.2 and stirred at 50°C for 2h;

[0042] Nano-silicon dioxide was added to the flame retardant system, and the mass ratio of nano-silicon dioxide to polydimethylsiloxane was 0.2:1.

[0043] The mixture was stirred at 30°C for 1 hour to obtain a uniform liquid, which was flame retardant solution B.

[0044] 3) Preparation of flame retardant wood

[0045] The raw wood is pretreated, and boards with a size of 20 mm (radial) × 100 mm (tangential) × 100 mm (longitudinal) are cut from the sapwood part above the breast height of the poplar, and are placed in the air to dry until the moisture content is ≤50%, and then the boards are placed in a forced air drying device and dried at 30°C until the moisture content is ≤15%. After the pretreatment, pretreated wood is obtained.

[0046] The pretreated wood was placed in the flame retardant solution A and immersed at negative pressure of -0.05 MPa at 30°C for 2 hours to obtain the impregnated wood.

[0047] The impregnated wood was taken out and dried in the shade for 3 hours, and then dried at 40°C to obtain dried wood;

[0048] Apply flame retardant solution B to the outer surface of the dried wood at a coating amount of 0.25 g / cm 2 Then place the coated wood in a fume hood to dry in the shade for 3 hours, then place it in a forced air drying oven to dry at 40°C, and then place it in a constant temperature and humidity chamber at 22°C and 65% humidity for 7 days.

[0049] Example 2

[0050] This embodiment provides a flame retardant anti-loss type high-efficiency flame retardant wood, and the preparation steps are as follows:

[0051] 1) Preparation of flame retardant solution A

[0052] Phytic acid and arginine were placed in a three-necked flask at a molar ratio of 1:1 and heated at 50°C for condensation and reflux for 2 hours to obtain NP flame retardant liquid. Ammonia water was added to adjust the pH value of the mixed solution to 6, which was flame retardant solution A.

[0053] 2) Preparation of flame retardant solution B

[0054] n-Hexane: polydimethylsiloxane: 1H,1H,2H,2H-perfluorodecyltriethoxysilane were mixed in a mass ratio of 20:3:0.3 and stirred at 50°C for 2h;

[0055] Nano-silicon dioxide was added to the flame retardant system, and the mass ratio of nano-silicon dioxide to polydimethylsiloxane was 0.3:1.

[0056] The mixture was stirred at 30°C for 1 hour to obtain a uniform liquid, which was flame retardant solution B.

[0057] 3) Preparation of flame retardant wood

[0058] The raw wood is pretreated, and boards with a size of 20 mm (radial) × 100 mm (tangential) × 100 mm (longitudinal) are cut from the sapwood part above the breast height of the poplar, and are placed in the air to dry until the moisture content is ≤50%, and then the boards are placed in a forced air drying device and dried at 30°C until the moisture content is ≤15%. After the pretreatment, pretreated wood is obtained.

[0059] The pretreated wood was placed in the flame retardant solution A and immersed at negative pressure of 50° C. and -0.1 MPa for 2 hours to obtain the impregnated wood.

[0060] The impregnated wood was taken out and dried in the shade for 3 hours, and then dried at 40°C to obtain dried wood;

[0061] Apply flame retardant solution B to the outer surface of the dried wood at a coating amount of 0.25 g / cm 2 Then place the coated wood in a fume hood to dry in the shade for 3 hours, then place it in a forced air drying oven to dry at 40°C, and then place it in a constant temperature and humidity chamber at 22°C and 65% humidity for 7 days.

[0062] Example 3

[0063] This embodiment provides a flame retardant anti-loss type high-efficiency flame retardant wood, and the preparation steps are as follows:

[0064] 1) Preparation of flame retardant solution A

[0065] Phytic acid and arginine were placed in a three-necked flask at a molar ratio of 1:1 and heated at 50°C for condensation and reflux for 2 hours to obtain NP flame retardant liquid. Ammonia water was added to adjust the pH value of the mixed solution to 6, which was flame retardant solution A (nitrogen phosphorus flame retardant A).

[0066] 2) Preparation of flame retardant solution B

[0067] n-Hexane: polydimethylsiloxane: 1H,1H,2H,2H-perfluorodecyltriethoxysilane were mixed in a mass ratio of 20:5:0.5 and stirred at 50°C for 2h;

[0068] Nano-silicon dioxide is added to the flame retardant system, and the mass ratio of nano-silicon dioxide to polydimethylsiloxane is 0.5:1.

[0069] The mixture was stirred at 30° C. for 1 h to obtain a uniform liquid, which was flame retardant solution B (Si-rich flame retardant B).

[0070] 3) Preparation of flame retardant wood

[0071] The raw wood is pretreated, and boards with a size of 20 mm (radial) × 100 mm (tangential) × 100 mm (longitudinal) are cut from the sapwood part above the breast height of the poplar, and are placed in the air to dry until the moisture content is ≤50%, and then the boards are placed in a forced air drying device and dried at 30°C until the moisture content is ≤15%. After the pretreatment, pretreated wood is obtained.

[0072] The pretreated wood was placed in the flame retardant solution A and immersed under negative pressure at 80° C. and 0.02 MPa for 2 hours to obtain the impregnated wood.

[0073] The impregnated wood was taken out and dried in the shade for 3 hours, and then dried at 40°C to obtain dried wood;

[0074] Apply flame retardant solution B to the outer surface of the dried wood at a coating amount of 0.25 g / cm 2 Then place the coated wood in a fume hood to dry in the shade for 3 hours, then place it in a forced air drying oven to dry at 40°C, and then place it in a constant temperature and humidity chamber at 22°C and 65% humidity for 7 days.

[0075] Comparative Example 1

[0076] In this comparative example, untreated natural wood (i.e., poplar wood material) was selected, and the size of the natural wood was 20 mm (radial direction)×100 mm (tangential direction)×100 mm (longitudinal direction).

[0077] Comparative Example 2

[0078] In this comparative example, raw wood was selected and pretreated, and boards with a size of 20 mm (radial) × 100 mm (tangential) × 100 mm (longitudinal) were cut from the sapwood above the breast height of the poplar, and the boards were placed in the air to dry until the moisture content was ≤50%, and then the boards were placed in a forced air drying device and dried at 30°C until the moisture content was ≤15%. After the pretreatment, pretreated wood was obtained.

[0079] The pretreated wood was placed in a phytic acid solution with a mass concentration of 70 wt%, and immersed at a negative pressure of -0.05 MPa at 30°C for 2 h;

[0080] The wood was taken out and dried in the shade for 3 hours, then dried at 40° C., and then placed in a constant temperature and humidity chamber at 22° C. and 65% humidity for 7 days to obtain phytic acid modified wood.

[0081] Comparative Example 3

[0082] This comparative example provides a flame retardant anti-loss type high-efficiency flame retardant wood, and the preparation steps are as follows:

[0083] 1) Preparation of flame retardant solution A

[0084] Phytic acid and arginine were placed in a three-necked flask at a molar ratio of 1:1 and heated at 50°C for condensation and reflux for 2 hours to obtain NP flame retardant liquid. Ammonia water was added to adjust the pH value of the mixed solution to 6, which was flame retardant solution A.

[0085] 2) Preparation of flame retardant wood

[0086] The raw wood is pretreated, and boards with a size of 20 mm (radial) × 100 mm (tangential) × 100 mm (longitudinal) are cut from the sapwood part above the breast height of the poplar, and are placed in the air to dry until the moisture content is ≤50%, and then the boards are placed in a forced air drying device and dried at 30°C until the moisture content is ≤15%. After the pretreatment, pretreated wood is obtained.

[0087] The pretreated wood was placed in flame retardant solution A and immersed in negative pressure at 30°C and -0.05Mpa for 2 hours; the wood was taken out and dried in the shade for 3 hours, then dried at 40°C, and then balanced in a constant temperature and humidity chamber at 22°C and 65% humidity for 7 days to obtain flame retardant solution A modified wood.

[0088] Moisture absorption and flame retardant loss resistance test

[0089] According to ASTM D3201 (ASTM 2003) "Standard Test Method for Moisture Absorption of Flame Retardant Wood and Wood Products", the moisture absorption rate of the modified wood sample was tested at a relative humidity of 92±2% and a temperature of 27±2°C. The sample size was 20×20×10mm. 3 (L×T×R). Referring to the AWPAE11 (AWPA2006) "Test Method for the Loss of Wood Preservatives" standard, the loss resistance of the modified wood sample was tested. Using the experimental equipment OCA25, under natural gas pressure, a 0.5 microliter water droplet was placed on the wood surface to test the initial contact of the water droplet on the surface of the modified wood sample. The test results are shown in Table 1:

[0090] Table 1 Moisture absorption and loss resistance of modified wood

[0091] Group Moisture absorption rate (%) Anti-loss rate (%) Initial contact angle (°) Example 1 9.23 85.2 155.6 Comparative Example 1 35.45 - 49.8 Comparative Example 2 54.72 1.61 59.2 Comparative Example 3 53.61 3.42 43.7

[0092] From Table 1 and Figure 1 It can be seen that the natural wood in Comparative Example 1 easily absorbs moisture under high humidity, and the surface contact angle is 49.8, which indicates that the natural wood itself contains hygroscopic groups and the wood surface is easily wetted by water.

[0093] The moisture absorption rate of water-soluble nitrogen-phosphorus flame retardant modified wood is higher than that of natural wood, and the flame retardant easily migrates to the wood surface with water, thereby losing. The surface contact angle of phytic acid modified wood in Comparative Example 2 is 59.2, indicating that the surface of phytic acid treated wood is easily wetted, and the phytic acid flame retardant is very easy to lose, and the anti-loss property is only 1.61%. The surface contact angle of the flame retardant wood in Comparative Example 3 is lower than that in Comparative Example 1, indicating that the flame retardant treated wood is more easily wetted and the flame retardant is easy to lose.

[0094] The flame retardant wood in Example 1 has a surface contact angle of more than 150°, indicating that it has super hydrophobicity, a large contact angle between a water droplet and the wood surface, and the wood is not easily soaked. The flame retardant has an anti-loss property of 85.2%; the hygroscopicity decreases by 73.96%, indicating that the flame retardant prevents moisture from entering the wood. The Si-rich flame retardant B and the nitrogen-phosphorus flame retardant A in this embodiment have a synergistic anti-loss effect on the modified wood.

[0095] Thermal stability test of modified wood

[0096] The thermal stability of the modified wood samples was tested and analyzed using a thermogravimetric analyzer TGA under nitrogen protection and air conditions. The test temperature range was 30-700°C, and the heating rate was 10°C / min. The TGA test results are shown in Table 2:

[0097] Table 2 Thermal stability test of modified wood

[0098]

[0099] TGA analysis can show that the mass of flame-retardant wood changes with increasing temperature in a nitrogen or air atmosphere. The faster the mass decreases, the lower the thermal stability of the material, which also means that the thermal decomposition reaction of the material during combustion is more violent and the flame retardancy is poor.

[0100] In comparative example 1, the natural wood reacted most violently at 290°C under air conditions, with the highest rate of thermal weight loss. By 700°C, the wood was almost completely thermally decomposed, with only 1.63% remaining.

[0101] In Comparative Example 2, due to the catalytic carbonization of phytic acid at a higher temperature, the thermal degradation reaction of the flame retardant wood is advanced. The temperature corresponding to the maximum thermal weight loss rate under air conditions is 245°C, and the residual carbon content at 700°C is 5.56%, which is higher than that of natural wood, but the effect is not significant.

[0102] In Comparative Example 3, the nitrogen-phosphorus flame retardant formed by the reaction of phytic acid and amino acid can provide a good flame retardant effect. The temperature at which the mass of the flame-retardant wood decreases by 5% is 130°C, which is significantly higher than that of Comparative Examples 1 and 2. The residual carbon content at 700°C reaches 8.5%, indicating that the synthetic nitrogen-phosphorus flame retardant has a good flame retardant effect.

[0103] In Example 1, the temperature at which the mass loss of the flame-retardant wood is 5% is 136°C (nitrogen) and 133°C (air), indicating that the thermal stability of the flame-retardant wood in both anaerobic and aerobic environments is significantly improved, and the flame-retardant wood is not prone to thermal decomposition. The residual carbon content of the flame-retardant wood at 700°C reaches 38.8% (nitrogen) and 18.27°C (air), which is 162.69% and 1020.89% higher than that of Comparative Example 1, respectively. Compared with Comparative Example 3 with a better flame retardant effect, the residual carbon content of the flame-retardant wood in Example 1 at 700°C is further improved, especially under air conditions, the residual carbon content increases by 114.94%. In Example 1, the silicon-containing flame retardant component in the hydrophobic coating forms a synergistic flame retardant effect with the nitrogen-phosphorus flame retardant, which jointly improves the thermal stability of the modified wood.

[0104] Flame retardant test

[0105] The oxygen index was measured using a fully automatic oxygen index tester in accordance with the national standard GB / T 2406-93. The sample size was 100×6×3mm. 3 (L×T×R). According to ISO 5660-2002, a cone calorimeter is used to test the heat and smoke release characteristics of the sample during combustion. The sample size is 100×100×14mm 3 (L×T×R), the radiation power is set to 50kW / m 2 . Limiting oxygen index, cone calorimetry test results such as Figure 2 shown.

[0106] Depend on Figure 2It can be seen that the ignition time of natural wood in Comparative Example 1 is only 13s, and the limiting oxygen index is 20%, indicating that natural wood is easily ignited in the air and there is a great fire hazard. The ignition time and limiting oxygen index of the nitrogen-phosphorus flame retardant modified wood in Comparative Example 3 are better than those in Comparative Example 2, indicating that the flame retardant effect of the nitrogen-phosphorus flame retardant synthesized in this embodiment is due to phytic acid. The limiting oxygen index of the flame-retardant wood in Example 1 is 58%, indicating that the flame-retardant wood will not be ignited under air conditions; the ignition time of the flame-retardant wood in Example 1 under fire environment (50kW, 780°C) is extended from 13s of natural wood to 24s, indicating that flame-retardant wood is of great significance in delaying fire and improving personal and property safety in a fire environment. In Example 1, there is a synergistic flame retardant effect between Si-rich flame retardant B and nitrogen-phosphorus flame retardant A.

[0107] Depend on Figure 3 It can be seen that the total heat release of the flame-retardant wood in Example 1 during the cone calorimetry test is lower than that of the comparative example. The total heat release curve in Example 1 can further prove that the Si-rich flame retardant B and the nitrogen-phosphorus flame retardant A in this example have a synergistic flame retardant effect on the modified wood.

[0108] Depend on Figure 4 It can be seen that the total smoke release of the wood sample in the comparative example is much higher than that in Example 1. The total smoke release of the flame-retardant wood in Example 1 within 0 to 500 seconds is reduced by 80.86% compared with that in Comparative Example 1. In particular, the total smoke release of the flame-retardant wood in Example 1 no longer increases after 160 seconds, indicating that the smoke release rate of the flame-retardant wood during this combustion process is close to 0. At this time, the silica and nitrogen-phosphorus flame retardant in the hydrophobic coating form a tight heat-insulating and oxygen-isolating barrier on the surface of the wood, reducing the thermal decomposition reaction of the internal material. At the same time, the nano-silicon dioxide in the barrier layer can absorb smoke, achieving a smoke-free effect when the flame-retardant wood burns.

[0109] Depend on Figure 5 It can be seen that the natural wood in Comparative Example 1 produces more carbon monoxide, and the carbon monoxide release peaks appear around 50s and 250s. After 400s, the natural wood in Comparative Example 1 has basically been completely burned, leaving very little charcoal and ash, so the carbon monoxide release rate is the lowest. The carbon monoxide release rate of the flame-retardant wood samples in Comparative Examples 2 and 3 after 400s is significantly higher than that of natural wood. Wood treated with nitrogen and phosphorus flame retardant modification is often not easy to burn fully, and oxygen-free combustion is often accompanied by the generation of more carbon monoxide. It is worth noting that the carbon monoxide release of the modified wood in Example 1 is low, especially the carbon monoxide release rate within 100 to 400s is only 0.018g / s, which is significantly lower than that of the comparative example. After the burning time is 400s, the modified wood in Example 1 is still incomplete combustion, but the carbon monoxide release rate is significantly lower than that of Comparative Examples 2 and 3.

[0110] Figure 4 and Figure 5 The results can support each other, and the Si-rich flame retardant B and the nitrogen-phosphorus flame retardant A in this embodiment have a synergistic smoke suppression effect on the modified wood.

[0111] The preferred embodiments of the present invention disclosed above are only useful to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing flame retardant anti-loss type high-efficiency flame retardant wood, characterized in that: The steps include: S1. Put the phytic acid solution and the amino acid solution into a reaction container according to a certain ratio, heat and condense the solution at a temperature of 20 to 80° C. for 0.5 to 4 hours, and then add ammonia water to adjust the pH value of the mixed solution to 5 to 7 to obtain a flame retardant solution A for standby use; S2, add polydimethylsiloxane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to n-hexane in sequence, stir at 20-80°C for 0.5-4h, then add nano-silicon dioxide, mix well, and stir at 20-80°C for 0.5-4h to obtain flame retardant solution B for standby use; S3, pre-treating the raw wood to obtain pre-treated wood; S4, firstly use the flame retardant solution A to impregnate the pretreated wood, then dry the obtained impregnated wood, and then use the flame retardant solution B to coat the obtained dried wood to obtain flame retardant wood.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass concentration of phytic acid in the phytic acid solution is 70 wt %, and the mass concentration of amino acids in the amino acid solution is 10 wt %.

3. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of phytic acid in the phytic acid solution to the amino acid in the amino acid solution is 1:1-2; the amino acid in the amino acid solution is at least one of lysine, arginine, glutamic acid, threonine, and phenylalanine.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of n-hexane, polydimethylsiloxane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane is 20:1-5:0.1-0.

5.

5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of nano-silicon dioxide to polydimethylsiloxane is 0.1-0.5:

1.

6. The preparation method according to claim 1, characterized in that: In step S3, the species of raw wood is poplar; the specific operation of pretreatment is: the newly felled poplar wood is sawn into boards with a thickness of ≤5 cm, placed in the air to dry until the moisture content is ≤50%, and then placed in a forced air drying device and dried at a temperature of 30-80°C to a moisture content of ≤15%.

7. The preparation method according to claim 1, characterized in that: In step S4, the specific operation of the impregnation treatment is: completely immerse the pretreated wood in a pressure impregnation tank filled with flame retardant solution A, control the impregnation temperature at 20 to 80°C, control the impregnation pressure at -0.1 to 0.05 MPa, and control the impregnation time at 0.5 to 4 hours.

8. The preparation method according to claim 1, characterized in that: In step S4, the specific operation of the drying treatment is: firstly, the impregnated wood obtained by the impregnation treatment with the flame retardant solution A is shade-dried for 2 to 4 hours, and then dried at a temperature of 40°C.

9. The preparation method according to claim 1, characterized in that: In step S4, the specific operation of the coating treatment is: evenly coating the flame retardant solution B on the outer surface of the dried plate obtained by the drying treatment, with a coating amount of 0.20-0.30 g / cm 2 ; Then dry the coated wood in the shade for 2 to 4 hours and dry it at 40°C; then place the wood in a constant temperature and humidity chamber and carry out moisture balance at 22°C and 65% humidity, with the balance time ≥80 hours.

10. A flame retardant anti-loss type high-efficiency flame retardant wood, prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Steel-wood structure

    CN121228797A